A religious history of the American people - Ahlstrom, Sydney E. (Yale University Press, 1972)
Provides a comprehensive survey of religious beliefs, practices, and trends in America and includes background information on secular movement and influences.
Keywords: United States -- Religion.; États-Unis -- Religion.; RELIGION -- History.; TRAVEL -- Special Interest -- Religious.; Religion; United States; United States -- Church history.; Geschichte; Kirchengeschichte; USA; Godsdiensten.; Religiao (Historia)